2010
DOI: 10.1021/ef101085j
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Clay Wettability and Process Variables on Separation of Diluted Bitumen Emulsion

Abstract: Initial processing of bitumen froth obtained using a water-based extraction process from Athabasca oil sands yields stable water-in-bitumen emulsions. When the bitumen is diluted with naphtha to reduce its viscosity and density, almost complete separation can be obtained with a demulsifier in the absence of clay solids. However, a "rag layer" persists between the oil and free water layers when clay solids are present. Effects of the naphtha/bitumen (N/B) ratio, demulsifier selection, and silicate dosage on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 17 publications
1
40
0
Order By: Relevance
“…From results of zeta potential measurements, silica with 3 µm in diameter in 0.01 MLB at pH~11 has a higher zeta potential in absolute value (−26.23 mV) than at pH~3 (−1.88 mV), which is close to ZPC [20]. …”
Section: Silica Stabilized Emulsionmentioning
confidence: 79%
See 1 more Smart Citation
“…From results of zeta potential measurements, silica with 3 µm in diameter in 0.01 MLB at pH~11 has a higher zeta potential in absolute value (−26.23 mV) than at pH~3 (−1.88 mV), which is close to ZPC [20]. …”
Section: Silica Stabilized Emulsionmentioning
confidence: 79%
“…Neutral conditions are more favorable to formation of stable emulsion than acid conditions. It is found that the edges of the kaolinite are positively charged, which may adsorb negatively charged carboxylate components of the oil and turn that portion of clay solids partially oil-wet [20,21]. As Figure 13a shows, the clay particles are simply depicted as round and most of it is in the continuous phase (oil) due to their hydrophobicity.…”
Section: Closing Remarksmentioning
confidence: 99%
“…13 The attached clays to the bitumen surface can also cause problems in bitumen froth treatment by forming a rag layer. [14][15][16] The mechanism for bitumen slime coating has recently been studied in detail by Masliyah et al using atomic force microscopy (AFM) and zeta potential distribution measurement. 12,[17][18][19][20][21][22][23] While oil sands ores are a complex mixture of clays including kaolinite, illite, chlorite, montmorillonite, not all the clays cause slime coating.…”
Section: Introductionmentioning
confidence: 99%
“…While pipeline deposition can lead to pipe plugging, adsorption onto clay solids modifies their wettability, decreasing efficiency of oil liberation from the solids and increasing solids partitioning at the oil-water interface. [14][15][16][17][18][19][20] In oil production, the formation of a complex multiphase dispersion layer in the middle of oil-water separation vessel, known as rag layers, is frequently encountered. 21,22 The rag layers are extremely stable multiemulsions with the stabilizing species identified as surfactants, asphaltenes and inorganic fine particles.…”
Section: Introductionmentioning
confidence: 99%